Quality of life through quality of information: proceedings of MIE2012 - Mantas, John; Andersen, Stig Kjær; Mazzoleni, Maria Cristina; Blobel, Bernd; Quaglini, Silvana; Moen, Anne (Studies in health technology and informatics, 2012)
Role of e-health in pursuing benefits in terms of quality of life for patients, health-care personnel, citizens and society
Includes bibliographical references and index. - Description based on PDF from IOS Press (viewed Aug. 24, 2012); title from PDF title page
Keywords: Electronic books -- Conference proceedings; Konferenzschrift